The Importance of Leadership Style, Characteristics and Work Environment for Creating Members' Performance - Dito Sigit Kuncoro; Harianto Respati; Mokhamad Nasir (Innovation Business Management and Accounting Journal, 2024)
partial effects of leadership style, individual characteristics, and work environment on the performance of Bogor Search and Rescue Air Unit personnel. This study also aims to determine which elements in leadership style, individual traits, and work environment influence members' performance in the Bogor Search and Rescue Air Unit. The research population and sample include 73 members of the Bogor Search and Rescue Air Unit who will be studied as a whole. This study employed descriptive analysis to assess the frequency distribution of respondents' answers to questionnaire results, as well as multiple linear regression analysis. The study's findings indicate that leadership style, individual traits, and work environment all have an impact on performance, both simultaneously and partially. This study found that leadership style has a significant impact on the performance. According to the findings of this study, the leadership style used should be charismatic or transformational, with a focus on members' individual character abilities and the implementation of a sense of openness between members and leaders of the Bogor Search and Rescue Air Unit, as well as the establishment of brotherly relationships among members.